The Dawn of a New Arctic Chessboard - Deheza, Elizabeth (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree of Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: The Arctic region is constantly changing and over the past decade has been re-launched to the forefront of modern geopolitics as climate change has increased the potential availability of natural resources and new shipping lanes. This has sparked the interest not only of the five polar coastal states (U.S., Russia, Canada, Norway and Denmark (Greenland)) and the Arctic Council; but also of other countries and non-state actors who wish to exert their influence on the region. Elevated interest in the area and the desire of outside actors to become involved, have the potential to completely alter the political dynamics of decision making processes. We demonstrate and quantify, by analysis of geopolitical and international relations theories, motivations of the main actors, and the development of a Chessboard Model based on game theory, that it is imperative for the polar coastal states to resolve their existing disputes and collaborate in the region if they are to discourage the involvement of Arctic "newcomers" and retain control of decision making processes in the Arctic.